Kembar Siam (Dicephalus Parapagus Dibrachius) - Primadella Fegita; Roza Sri Yanti (Majalah Kedokteran Indonesia, 2018)
Introduction : Conjoined twin is a form of congenital anomaly that take the attention of the medical world. Approximately 75% of conjoined twins are women and 70% are attached to the chest (thorachophagus) or abdomen (omphalophagus). Conjoined twins can be divided into 2 categories, which are symmetrical twins and asymmetric twins. The longer the embryological separation takes place, the more complicated the twin attachments that will occur.Case Presentation: A 31-year-old female patient was referred from Fetomaternal Polyclinic to M. Djamil Hospital Padang ward on August 28, 2017 at 11.00 with a diagnosis of G4P3A0H3 31- 32 weeks gravid + Conjoined Twins (Dicephalus Parapagus Dibrachius) + Polyhydramnios.Conclusions: Multifetus pregnancy is considered high-risk because it increases maternal and perinatal morbidity and mortality. In conjoined twins cases, multidisciplinary approach needs to be done for a better prognosis for the mother and baby.